Targeted Therapy with Anlotinib for a Patient with an Oncogenic FGFR3‐TACC3 Fusion and Recurrent Glioblastoma - Wang, Yong (Oncologist, 2020)
We describe a case of recurrent glioblastoma treated with anlotinib in this report. The patient was administered anlotinib 12 mg p.o. once every day (days 1–14, with a 21‐day cycle) (anlotinib clinical study NCT04004975) and oral temozolomide chemotherapy 100 mg/m(2) (days 1–7, days 15–21, 28‐day cycle; 12 cycles). After 2 months of therapy, the patient achieved a partial response that has been maintained for >17 months of follow‐up. Molecular characterization confirmed the presence of a TERT promoter mutation, wild‐type IDH1/2, an FGFR3‐TACC3 fusion, and FGFR3 amplification in the patient. Anlotinib is a multitarget tyrosine kinase inhibitor that was originally designed to inhibit VEGFR2/3, FGFR1–4, PDGFRα/β, and c‐Kit. Patients with TERT promoter mutations and high‐grade IDH‐wild‐type glioma have shorter overall survival than patients with IDH‐wild‐type glioma without TERT promoter mutations. However, this patient had a favorable clinic outcome, and FGFR3‐TACC3 fusion may be a new marker for treatment of glioma with anlotinib. KEY POINTS: This case study is believed to be the first report that FGFR3‐TACC3 fusion could be a novel indication to treat recurrent glioblastoma with the drug anlotinib. This case exhibited an exceptional response (maintained partial response >17 months) after 2‐month combined therapy of anlotinib and oral temozolomide chemotherapy. This case also underscores the importance of molecular diagnosis for clinically complex cases. Tumor tissue‐based assessment of molecular biomarkers in brain tumors has been successfully translated into clinical application.